2011
DOI: 10.4314/jopat.v14i1.69411
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of <i>Cassia sieberiana</i> Root Bark Extract on Various Experimental Gastric Ulcer Models in Rats

Abstract: The antiulcerogenic effects of the root bark extract of C. sieberiana were studied using various gastric ulcer models in rats. This was to support the rational phytotherapeutic use of Cassia sieberiana root bark extract in managing gastric ulcer. The cytoprotective ability of the extract was tested using the HCl/ethanol and the indomethacin-HCl/ethanol induced gastric lesion models. The healing ability of the extract was tested using the acetic acid induced model. Ulcer index, gastric HCl output, mucus product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…This data suggests that C. sieberiana root bark extract possesses strong gastro-cytoprotective properties against ethanol-induced gastric ulcers. This is in agreement with earlier reports that the root bark extract possesses anti-ulcerogenic properties in other induced gastric ulcer animal models [8] and is supported by the inhibition of decrease of the anti-oxidative enzymes SOD, CAT and GPx.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This data suggests that C. sieberiana root bark extract possesses strong gastro-cytoprotective properties against ethanol-induced gastric ulcers. This is in agreement with earlier reports that the root bark extract possesses anti-ulcerogenic properties in other induced gastric ulcer animal models [8] and is supported by the inhibition of decrease of the anti-oxidative enzymes SOD, CAT and GPx.…”
Section: Discussionsupporting
confidence: 93%
“…were obtained from the grounds of the University of Ghana, authenticated at the Ghana herbarium and prepared as previously described by Nartey et al [8]. Briefly, chopped fresh root barks of C. sieberiana (750 g) were grounded and mixed with 1L of water and left to stand for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the Centre for Scientific Research into Plant Medicine (CSRPM) in Ghana, an aqueous suspension of the powdered roots bark is used to manage abdominal colic and pains associated with the joints. Earlier studies we conducted indicated that the aqueous roots bark extract of C. sieberiana possesses anti-ulcerogenic properties against gastric ulcers induced by various methods [ 2 ].…”
Section: Introductionmentioning
confidence: 99%